Defected ground structure based wideband microstrip low‐pass filter for wireless communication. Issue 5 (May 2017) - Vala, Alpesh; Patel, Amit; Goswami, Riddhi; Mahant, Keyur
ABSTRACT: This article represents microstrip low‐pass filter using defected ground structure (DGS) for the wireless communication application. DGS is used as the basic building block for the realisation of a low‐pass filter. A low‐Pass filter with a −3 dB cutoff frequency of 3.5 GHz has been designed and simulated using high frequency structure simulator. Tuning of frequency is carried out by changing the dimension of DGS. An equivalent LC circuit of proposed structure is derived and simulated it with advanced design system software. Proposed low‐pass filter has been fabricated and provides better performance with compact size; it can be used in wireless communication application such as PCS‐1900, UMTS, Bluetooth, WLAN, Wi‐max, IMS, and RFID etc. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:993–996, 2017